Familial history of migraine influences habituation of visual evoked potentials. (October 2017) - Lisicki, Marco; Ruiz-Romagnoli, Emiliano; D'Ostilio, Kevin; Piedrabuena, Raúl; Giobellina, Roberto; Schoenen, Jean; Magis, Delphine
Background: Lack of habituation of visual evoked potentials (VEP) is a common finding in migraine patients between attacks. Previous studies have suggested an electrophysiological familial aggregation pattern associated with migraine. The aim of this study was to evaluate the influence of a positive familial history of migraine on VEP amplitude and habituation. Methods: We recorded six blocks of 100 VEP during continuous pattern-reversal stimulation in 30 patients with migraine between attacks (MO) and in 30 healthy volunteers, of whom 15 had a first-degree relative suffering from migraine (HVm) and 15 had not (HV). Results: Both MO and HVm had a significant deficit of VEP habituation and similarly reduced N1-P1 first block amplitudes, compared to HV (habituation slope: MO = 0.033, HVm = 0.021, HV = −0.025, HV vs. MO p = 0.002, HV vs. HVm p = 0.036; mean N1-P1 amplitude in the first block: MO = 9.08 µV, HVm = 9.29 µV, HV = 12.19 µV. HV vs. MO p = 0.041, HV vs. HVm p = 0.076). The first block N1-P1 amplitude was negatively correlated with the habituation slope for both MO (ρ = −.44, p = 0.015) and HVm (ρ = −.56, p = 0.031) while no significant correlation was found in HV (ρ = .17, p = 0.53). There were no differences in VEP latencies between the groups. Conclusions: Our study suggests that lack of habituation of visual evoked potentials is probably a genetically determined endophenotypic trait that is associated with both migraine and migraine susceptibility. We hypothesize that genetic diversity of populations could account for some of the discrepancies between electrophysiological studies performed in migraine and for interindividual variations among the subgroups.